2016
DOI: 10.1177/1059840516674053
|View full text |Cite
|
Sign up to set email alerts
|

Students With Chronic Conditions: Experiences and Challenges of Regular Education Teachers

Abstract: School nurses have observed the increasing prevalence of children with chronic conditions in the school setting; however, little is known about teacher experiences with these children in their regular classrooms. The purpose of this mixed-method study was to describe the experiences and challenges of regular education teachers when they have students with chronic conditions in their classroom and implications for the school nurse. The national sample consisted of regular education teachers. The methodologies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
2
19
0
2
Order By: Relevance
“…Regarding the second research question, which sought to determine the frequency of teacher preparation programs that explicitly advertise an emphasis on training educators on the schoolrelated needs of students with a chronic health condition, few programs specifically call this out as an area of expertise of specialization within their program descriptions or marketing materials. This finding was consistent with previous literature indicating that teachers do not receive training and are not prepared to meet the needs of children with chronic illnesses (Clay et al, 2004;Selekman, 2017). Educators have highlighted the value of this training for improving children's educational experiences and increasing teacher confidence and abilities to meet the needs of all children in their classroom (Cunningham & Wodrich, 2006;Prevatt et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the second research question, which sought to determine the frequency of teacher preparation programs that explicitly advertise an emphasis on training educators on the schoolrelated needs of students with a chronic health condition, few programs specifically call this out as an area of expertise of specialization within their program descriptions or marketing materials. This finding was consistent with previous literature indicating that teachers do not receive training and are not prepared to meet the needs of children with chronic illnesses (Clay et al, 2004;Selekman, 2017). Educators have highlighted the value of this training for improving children's educational experiences and increasing teacher confidence and abilities to meet the needs of all children in their classroom (Cunningham & Wodrich, 2006;Prevatt et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…While this research study utilized multiple methods to examine the identified research questions, a primary limitation emerged due to the small sample size of survey respondents. However, findings were consistent with other studies that have examined similar content (e.g., Clay et al, 2004;Selekman, 2017). Additional methodology limitations were inherent in the curriculum review process, such as the known variation associated with curriculum and online availability and completeness of such content; triangulation and member-checking with interview data helped to validate this process to the greatest extent possible.…”
Section: Limitationssupporting
confidence: 84%
See 1 more Smart Citation
“…24 This unpreparedness can be explained by the teacher’s unfamiliarity with the condition, inadequate time to maintain individualized focus, and/or unavailability of appropriate study material for support. 25,26…”
Section: Introductionmentioning
confidence: 99%
“…In educational system, educational personnel have limited of understanding as to the condition-related needs of students with chronic conditions and disabilities who require treatments while in school (Bishop and Boag, 2006;Selekman, 2017). For example, the educational personnel may not fully understand the student's need to visit the school nurse's office which can cause delays in arriving on time to their classes and may view it negatively as being deliberate.…”
mentioning
confidence: 99%